Personality Traits, Gender and Organisational Factors as Correlates of Communication Styles Among Management Staff in Public Organisations in Southwestern Nigeria (2013)
The negative performance of most public organisations in Southwestern Nigeria are partly attributed to poor information sharing system arising from the defective Communication Styles (CS) being adopted by their management staff. Literature has shown that these defective CS can be corrected with a better understanding of factors such as personality traits, organisational and gender factors. However, previous studies on improving the CS and general performance in the public service have focused more on other issues such as culture, emotional intelligence and professional training than on the combined predictive effects of these factors. This study, therefore, examined the predisposing effects of personality traits (openness, extraversion, agreeableness, neuroticism, conscientiousness), organisational (work overload, role ambiguity, organisational culture) and gender (gender-identity, gender-labelling, gender-linked conducts, peer preference and determinative role) factors on the communication styles of public management staff in Southwestern Nigeria. A descriptive survey research design was adopted. Purposive sampling technique was used to select six best performing public organisations in each of the six states of the Southwest; while the entire 1,910 management staff on grade level 12 and above in these organisations were chosen as respondents. Four instruments were used: Gender Factors Questionnaire (r= 0.78), Personality Traits Inventory (r=0.86), Organisational Factors Scale (r=0.92) and Management Communications Inventory (r=0.93). These were complemented with 12 sessions of in-depth interviews with permanent secretaries and senior directors. One research question was answered and four hypotheses tested at 0.05 significance level. Data were analysed using descriptive statistics, percentages, Pearson‟s product moment correlation, multiple regression and content analysis. Personality Traits (PT), Gender Factors (GF) and Organisational Factors (OF) had a significant joint prediction on communication styles (CS) (F(13,1896) = 27.01; R = .395, R2 = .156, Adj. R2 = .150). Their relative contributions were ranked: PT (β= 0.335), GF (β=-.103) and OF (β=0.069). A significant joint effect of PT on CS was observed (F(5,1904) = 62.428; R = .375, R2 = .141, Adj. R2 = .139); with following relative contributions: Agreeableness (β=0.342), Conscientiousness (β=0.192), Openness (β=0.067), Extraversion (β=-0.095) and Neuroticism (β=-0.072). The GF had a joint significant effect on CS (F(5,1904) = 16.771) and accounted for about 4.0% of the variation. Their relative contributions were: gender-identity (β=0.139), determinative role (β=0.126), gender-linked conducts (β=0.096), gender-labelling (β=-0.170) and peer preference (β=-0.043). There was also a significant joint effect of OF on CS (F(3,1906) = 36.56; R = .233, R2 = .054, Adj. R2 =.053). Their relative contributions were: role ambiguity (β=0.157), work overload (β=0.148) and organisational culture (β=0.143). Interviews revealed that management staff communication style in public organisations was not exclusively a gender issue but a combination of some factors, particularly those relating to personality and organisation. Personality traits, organisational and gender factors impacted positively on the communication styles of public management staff in Southwestern Nigeria. Public organisations, therefore, should ensure flexible and adaptive communication styles.